The best story - Spinelli, Eileen; Wilsdorf, Anne (New York : Dial Books for Young Readers, 2008)
When a contest at the local library offers a prize for the best story, a girl tries to write one using her family's suggestions, but her story does not seem right until she listens to her heart.
2.7
K-3
K-3
390
Keywords: Creative writing -- Juvenile fiction; Creative writing -- Fiction; Creative writing -- Fiction